Gallbladder cancer- causes, symptoms and chirurgical treatment: systematic review - Magdalena Żukowska; Anna Fabian-Danielewska; Piotr Krajewski; Katarzyna Korabiusz; Agata Krajewska (Kazimierz Wielki University, 2018)
Gallbladder cancer (GBC) is the most common cancer of bile ducts. This is one of the worst prognostic tumors of the digestive tract. The disease is asymptomatic for a long time, which is why it is detected in a high stage, which shortens the chances of healing. Surgery has a fundamental role in the treatment of gallbladder cancer. The patient survival prognosis depends mainly on the local severity of the disease, distant metastases and the radicality of surgical resection (R0).